ANALISIS PERSEDIAAN KEBUTUHAN GALANGAN (PLAT KAPAL) DENGAN METODE EOQ PADA PT PENGERUKAN INDONESIA - Vivian Karim Ladesi; Tasya Agustin; Winoto Hadi (Universitas Negeri Jakarta, 2021)
Inventory is one of the fundamental problems in a business. Without inventory, a business will be faced with a variety of problems, for example, not having the option to fulfill client orders that lead to loss of client trust, inhibiting interaction creation, etc. Therefore, this study will analyze the management of ship plate inventory at PT Pengerukan Indonesia. There is a technique used to control the supply of stock, namely the